Breast hamartoma: a clinicopathologic analysis of 27 cases and a literature review (Clinics, 2014)
OBJECTIVES: Breast hamartoma is an uncommon breast tumor that accounts for approximately 4.8% of all benign breast masses. The pathogenesis is still poorly understood and breast hamartoma is not a well-known disorder, so its diagnosis is underestimated by clinicians and pathologists. This study was designed to present our experience with breast hamartoma, along with a literature review. METHOD: We reviewed the demographic data, pathologic analyses and imaging and results of patients diagnosed with breast hamartoma between December 2003 and September 2013. RESULTS: In total, 27 cases of breast hamartoma operated in the Ankara University Medicine Faculty's Department of General Surgery were included in the study. All patients were female and the mean age was 41.8±10.8 years. The mean tumor size was 3.9±2.7 cm. Breast ultrasound was performed on all patients before surgery. The most common additional lesion was epithelial hyperplasia (22.2%). Furthermore, lobular carcinoma in situ was identified in one case and invasive ductal carcinoma was observed in another case. Immunohistochemical staining revealed myoid hamartoma in one case (3.7%). CONCLUSION: Breast hamartomas are rare benign lesions that may be underdiagnosed because of the categorization of hamartomas as fibroadenomas by pathologists. Pathologic examinations can show variability from one case to another. Thus, the true incidence may be higher than the literature indicates.